Three-dimensional finite element modelling for additive manufacturing of Ti-6Al-4V components: Effect of scanning strategies on temperature history and residual stress - Zhou, Jinbiao; Barrett, Richard A.; Leen, Sean B. (Journal of advanced joining processes, 2022)
A key challenge for metal additive manufacturing is the requirement to adapt process-structure-property methods currently under development to realistic, complex geometries. Of specific concern in the present work is the requirement for accurate computation in such realistic geometries of (i) thermal histories, to facilitate microstructure prediction, and hence, mechanical properties, and (ii) residual stresses, as required for accurate assessment and design for structural integrity, such as fatigue cracking. This paper presents three-dimensional, finite element modelling for simulation of a realistic Ti-6Al-4V component using directed energy deposition. The predicted results are successfully validated against published experimental and numerical data. The effects of different scanning strategies on temperature histories and residual stresses are investigated as a basis for identification of optimal manufacturing protocols. Finally, fatigue life predictions of the Ti-6Al-4V component have been considered based on the Basquin-Goodman equation with the effect of residual stress taken into account.